Roles of the gut microbiota in severe SARS-CoV-2 infection. (February 2022) - Liu, Yiran; Kuang, Dan; Li, Dan; Yang, Ju; Yan, Jiai; Xia, Yanping; Zhang, Feng; Cao, Hong
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide. The pathophysiological mechanisms linking gut dysbiosis and severe SARS-CoV-2 infection are poorly understood, although gut microbiota disorders are related to severe SARS-CoV-2 infections. The roles of the gut microbiota in severe SARS-CoV-2 infection were compared with those in respiratory viral infection, which is an easily understood and enlightening analogy. Secondary bacterial infections caused by immune disorders and antibiotic abuse can lead to dysregulation of the gut microbiota in patients with respiratory viral infections. The gut microbiota can influence the progression of respiratory viral infections through metabolites and the immune response, which is known as the gut–lung axis. Angiotensin-converting enzyme 2 is expressed in both the lungs and the small intestine, which may be a bridge between the lung and the gut. Similarly, SARS-CoV-2 infection has been shown to disturb the gut microbiota, which may be the cause of cytokine storms. Bacteria in the gut, lung, and other tissues and respiratory viruses can be considered microecosystems and may exert overall effects on the host. By referencing respiratory viral infections, this review focused on the mechanisms involved in the interaction between SARS-CoV-2 infections and the gut microbiota and provides new strategies for the treatment or prevention of severe SARS-CoV-2 infections by improving gut microbial homeostasis. Graphical Abstract: ga1 Highlights: To better understand roles of the gut microbiota in SARS-CoV-2 infection, respiratory viruses were used as a reference. SARS-CoV-2 infection can disturb the gut microbiota, potentially leading to cytokine storms and gut–lung axis dysbiosis. Maintaining homeostasis of the gut microbiota is required for treating severe COVID-19.